2023
DOI: 10.1021/acs.orglett.3c02949
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Enantioselective Macrocyclization from Dynamic Imine Formation: Chemo- and Enantioselective Fluorescent Recognition of Lysine

Yifan Mao,
Stephanie Davis,
Lin Pu

Abstract: The dynamic covalent chemistry of imines is utilized to conduct a regioselective as well as enantioselective synthesis of an unsymmetric (C 1) chiral macrocycle from the reaction of an unsymmetric (C 1) chiral dialdehyde, (S)-4, that contains a salicylaldehyde unit and a benzaldehyde unit, with lysine, an unsymmetric (C 1) chiral diamine. The enantioselectivity is further enhanced in the presence of Zn2+. Compound (S)-4 in combination with Zn2+ is found to be a highly chemoselective as well as enantioselective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“… Treatment of the THF solution of the BINOL monoMOM ether with 3.2 equiv of n BuLi at 0 °C to room temperature followed by the addition of DMF gave the monoaldehyde compound ( S )- 263 in 62% yield over the three steps (Scheme ). This compound and its enantiomer served as the precursor to a variety of BINOL-aldehyde-based fluorescent probes such as compounds ( S , S )- 264 , ( S )- 265a , ( S )- 265b , and ( R , R , R )- 266 for the recognition of amino acids and metal ions.…”
Section: Ortho-lithiation At 3-positionmentioning
confidence: 99%
“… Treatment of the THF solution of the BINOL monoMOM ether with 3.2 equiv of n BuLi at 0 °C to room temperature followed by the addition of DMF gave the monoaldehyde compound ( S )- 263 in 62% yield over the three steps (Scheme ). This compound and its enantiomer served as the precursor to a variety of BINOL-aldehyde-based fluorescent probes such as compounds ( S , S )- 264 , ( S )- 265a , ( S )- 265b , and ( R , R , R )- 266 for the recognition of amino acids and metal ions.…”
Section: Ortho-lithiation At 3-positionmentioning
confidence: 99%
“…Yu et al [ 31 ] synthesized a small molecule gel based on BINOL phosphoric acid, which improved the gelation ability by complexing with Cu 2+ ; L -histidine was highly sensitive to the formed organometallic gel and caused it to undergo gel collapse, while D -histidine did not affect it, enabling the enantiomeric recognition of histidine. Pu et al [ 32 ] utilized the dynamic public chemistry of imines and found that the bis-aldehyde structure with BINOL as the substrate could undergo regioselective and enantioselective macrocyclization reactions with chiral diamines, whereas better enantioselectivity with Zn 2+ coordination allowed high chemoselectivity and enantioselectivity for lysine.…”
Section: Introductionmentioning
confidence: 99%